Two wrongs make a right: heat stress reversion of a male-sterile Brassica napus line. (28th February 2022) - Schuhmann, Petra; Engstler, Carina; Klöpfer, Kai; Gügel, Irene L; Abbadi, Amine; Dreyer, Felix; Leckband, Gunhild; Bölter, Bettina; Hagn, Franz; Soll, Jürgen; Carrie, Chris
Abstract : We have identified Tic40 as the restorer gene for the MSL system and hypothesize that heat treatment can also restore fertility via a cell cycle-induced developmental slow down. Abstract: Male-sterile lines play important roles in plant breeding to obtain hybrid vigour. The male sterility Lembke (MSL) system is a thermosensitive genic male sterility system of Brassica napus and is one of the main systems used in European rapeseed breeding. Interestingly, the MSL system shows high similarity to the 9012AB breeding system from China, including the ability to revert to fertile in high temperature conditions. Here we demonstrate that the MSL system is regulated by the same restorer of fertility gene BnaC9-Tic40 as the 9012AB system, which is related to the translocon at the inner envelope membrane of chloroplasts 40 (TIC40) from Arabidopsis. The male sterility gene of the MSL system was also identified to encode a chloroplast-localized protein which we call BnChimera; this gene shows high sequence similarity to the sterility gene previously described for the 9012AB system. For the first time, a direct protein interaction between BnaC9-Tic40 and the BnChimera could be demonstrated. In addition, we identify the corresponding amino acids that mediate this interaction and suggest how BnaC9-Tic40 acts as the restorer of fertility. Using an RNA-seq approach, the effects of heat treatment on the male fertility restoration of the C545 MSL system line were investigated. These data demonstrate that many pollen developmental pathways are affected by higher temperatures. It is hypothesized that heat stress reverses the male sterility via a combination of slower production of cell wall precursors in plastids and a slower flower development, which ultimately results in fertile pollen. The potential breeding applications of these results are discussed regarding the use of the MSL system in producing thermotolerant fertile plants.